Outcomes of combining a trifocal and a low-addition bifocal intraocular lens in patients seeking spectacle independence at all distances - Tarib, Imane; Breyer, Detlev Richard Hans; Höhn, Fabian; Kretz, Florian Tobias Alwin (Journal of cataract and refractive surgery, 2019)
Purpose - To assess the visual and refractive outcomes and patient satisfaction after cataract surgery in patients with a diffractive multifocal intraocular lens (IOL) with a low addition (add) power (+2.75 diopters [D]) (Tecnis ZKB00) in the dominant eye and a diffractive trifocal IOL (AT LISA tri 839MP) in the nondominant eye. - Setting - Augenärzte Gerl, Kretz, and Kollegen, Head Office, Ahaus, Germany. - Design - Prospective case series. - Methods - All patients had implantation of the low-add multifocal IOL in the dominant eye and a trifocal IOL in the fellow eye. Patients were evaluated preoperatively and 3 months postoperatively for monocular and binocular uncorrected distance visual acuity (UDVA), corrected distance visual acuity, intermediate and near visual acuities, the binocular defocus curve, and manifest refraction. Dysphotopic phenomena were objectively evaluated and subjective patient satisfaction questionnaires administered. - Results - The study included 42 patients (84 eyes). The mean postoperative spherical equivalent was −0.06 D ± 0.57 (SD). The binocular visual acuities were 0.00 ± 0.05 logarithm of the minimum angle of resolution (logMAR) (UDVA), 0.19 ± 0.11 logMAR (uncorrected intermediate visual acuity at 80 cm), 0.16 ± 0.10 logMAR (distance-corrected intermediate visual acuity at 80 cm), 0.11 ± 0.09 logMAR (uncorrected near visual acuity at 40 cm), and 0.08 ± 0.09 logMAR (distance-corrected near visual acuity at 40 cm). The binocular defocus curve showed a visual acuity of 0.20 logMAR or better between +0.50 D and −3.00 D. Of the patients, 92%, 92%, and 75% reported never wearing spectacles for distance, intermediate, or near distance, respectively. - Conclusion - The mix-and-match approach seemed to provide functional visual performance at all distances while achieving spectacles independence in the majority of patients.